The relationship between attention-deficit/hyperactivity disorder and perceived locus of control in boys. - Bivens, Mark (Curtin University, 2000)
The research examines the relationship between the two variables Attention- Deficit/Hyperactivity Disorder (A-D/HD) and Locus of Control in boys identified with A- D/HD.The major issues addressed are: the extent to which attentional deficit predicts external Locus of Control and the effect of a cognitive-behavioural intervention on boys with A- D/HD and a highly externalised Locus of Control. Reducing the externality of Locus of Control is seen as an innovative means of addressing some behavioural aspects of A-D/HD.The study involved 77 A-D/HD boys with A-D/HD and 23 boys who were not A-D/HD, but who demonstrated similar levels of disruptive behaviours, from schools in Western Australia. Australian norms were established for the Locus of Control instrument (CNS-IE) using 300 male classmates of the participants.Each boy was assessed by parents and teachers on established measures of A-D/HD (the Child Behavior Checklist (CBCL) and the Attention Deficit Disorders Evaluation Scale (ADDES)). The boys completed the CNS-IE both before and after the intervention. The boys with A-D/HD were medicated with Dexamphetamine or Ritalin, as prescribed by an appropriate medical practitioner.The association of A-D/HD diagnostic subtypes, (Predominantly Inattentive Type, Predominantly Hyperactive Type, Combined Type) with Locus of Control was also investigated.The results demonstrate that a significant (p < 0.001) correlation exists between attention deficit (assessed by the two parallel measures, CBCL and ADDES) and Locus of Control. The Locus of Control of boys with A-D/HD was significantly (p < 0.001) more external than that of the non-A-D/HD boys. This finding held true for each of the three A-D/HD subtypes when they were compared to the non-A-D/HD group.Participation in the cognitive behavioural intervention (the Stop, Think, Do program) significantly (p < 0.001) reduced the level of externality of Locus of Control in all groups of subjects.The research also examined the relationship between parents and teachers ratings of the same individual's behaviour. Ratings were found to be highly consistent between both groups. Parent ratings of inattention appear to be particularly salient both in identifying boys with an associated external Locus of Control and as an indicator of A-D/HD.The results of the research support the use of appropriate cognitive behavioural interventions in addressing self-regulation and responsibility, the central issues put forward in the Behavioural Disinhibition model of A-D/HD.Implications for the management of A-D/HD in the long term are also addressed. A multi- modal model involving medication and two stages of cognitive-behavioural intervention is recommended, where a cognitive behavioural intervention is used initially to develop a more internal Locus of Control, this being followed by a reframing program to sustain and develop more adaptive perceptions and behaviours.